1985
DOI: 10.1152/jappl.1985.59.4.1298
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exercise training on antioxidant enzymes and cardiotoxicity of doxorubicin

Abstract: The purpose of this study was to correlate the exercise-induced changes of oxidant stress enzymes with possible modification of the response to the putative oxidant stressor doxorubicin. Enzymatic and histological changes were studied in mice placed on a 21-wk swim training program (1 h/day, 5 days/wk) with and without anthracycline administration. Doxorubicin (4 mg/kg) was administered intravenously through a tail vein on 10 separate days over a 7-wk period (twice weekly during weeks 10, 11, 14, 15, and 16). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
2

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(89 citation statements)
references
References 0 publications
6
80
1
2
Order By: Relevance
“…Previous studies have shown that endurance training attenuates DOX-induced cardiac damage, diminishing the increased biochemical and morphological signs of toxicity induced by in vivo DOX treatment (2,26). However, no data are available concerning the cross-tolerance effect of moderate endurance training on DOX-induced mitochondrial malfunction.…”
Section: Overview Of the Principal Findingsmentioning
confidence: 99%
“…Previous studies have shown that endurance training attenuates DOX-induced cardiac damage, diminishing the increased biochemical and morphological signs of toxicity induced by in vivo DOX treatment (2,26). However, no data are available concerning the cross-tolerance effect of moderate endurance training on DOX-induced mitochondrial malfunction.…”
Section: Overview Of the Principal Findingsmentioning
confidence: 99%
“…Exercise training is one such intervention that shows promise in combating multiple aspects of DOX-induced cardiotoxicity by improving antioxidant status, 28 attenuating apoptotic pathways, 29 and preserving contractile protein expression. 21 In addition, our laboratory has reported that long-term exercise preconditioning protected against earlyonset DOX cardiotoxicity up to 10 days following treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Results from previous studies analyzing the response of liver antioxidants activity to exercise training are disparate. Increases [23][24][25], and decreases in this parameter have been described [26]. Nevertheless, most authors have reported absence of variations [27,28].…”
Section: Alt (Iu/l) Ast (Iu/l) Alp (Iu/l)mentioning
confidence: 99%